2022
DOI: 10.1136/jitc-2021-003264
|View full text |Cite
|
Sign up to set email alerts
|

The tumor-targeted CD40 agonist CEA-CD40 promotes T cell priming via a dual mode of action by increasing antigen delivery to dendritic cells and enhancing their activation

Abstract: Tumor-targeted CD40 agonism represents an attractive strategy for cancer immunotherapy (CIT) as it promotes dendritic cell (DC) activation and concomitant tumor-specific T cell priming without causing systemic side effects. We developed the bispecific CD40 agonistic antibody CEA-CD40, which triggers CD40 stimulation exclusively in the presence of carcinoembryonic antigen (CEA), a glycoprotein specifically expressed on tumor cells. In this study, we demonstrate that CEA-CD40 can enable potent in vitro DC activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Functional assays using a limited set of primary human cancer samples confirmed that the CEA levels in patients with colorectal cancer are sufficient to mediate CD40 clustering and demonstrated that tumor infiltrating immune cells can be activated using Neo-X-Prime bsAbs. Our hypothesis is that the increased antitumor effects of Neo-X-Prime bsAbs compared with the mAbs is 24 In addition, the ability of CD40 to target tumor antigens for cross-presentation has been demonstrated previously using CD40 antibodies fused to tumor antigen peptides, resulting in efficient priming and activation of CD8 + T cells indicating that CD40 is superior to other DC targets in this regard. 11 Taken together, these data support the hypothesis that CD40-directed uptake of tumor material and priming of tumor antigen-specific CD8 + T cells contributes to the superior antitumor effect of CD40×EpCAM compared with CD40 mAb.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Functional assays using a limited set of primary human cancer samples confirmed that the CEA levels in patients with colorectal cancer are sufficient to mediate CD40 clustering and demonstrated that tumor infiltrating immune cells can be activated using Neo-X-Prime bsAbs. Our hypothesis is that the increased antitumor effects of Neo-X-Prime bsAbs compared with the mAbs is 24 In addition, the ability of CD40 to target tumor antigens for cross-presentation has been demonstrated previously using CD40 antibodies fused to tumor antigen peptides, resulting in efficient priming and activation of CD8 + T cells indicating that CD40 is superior to other DC targets in this regard. 11 Taken together, these data support the hypothesis that CD40-directed uptake of tumor material and priming of tumor antigen-specific CD8 + T cells contributes to the superior antitumor effect of CD40×EpCAM compared with CD40 mAb.…”
Section: Discussionmentioning
confidence: 86%
“…Our hypothesis is further supported by in vitro data recently published by Sum et al , demonstrating that CD40×CEA antibodies can promote loading of DC with tumor antigen resulting in enhanced tumor-specific cross-priming. 24 In addition, the ability of CD40 to target tumor antigens for cross-presentation has been demonstrated previously using CD40 antibodies fused to tumor antigen peptides, resulting in efficient priming and activation of CD8 + T cells indicating that CD40 is superior to other DC targets in this regard. 11 Taken together, these data support the hypothesis that CD40-directed uptake of tumor material and priming of tumor antigen-specific CD8 + T cells contributes to the superior antitumor effect of CD40×EpCAM compared with CD40 mAb.…”
Section: Discussionmentioning
confidence: 88%
“…Such approaches have been expedited by the innovative design of bispecific antibodies targeting tumor-associated antigens or dendritic cell surface markers, in addition to CD40, or by selective delivery of CD40 agonists into the tumor tissue. [42][43][44][45][46][47][48] The practical translation of our RBC-based macrophage reprogramming approach has to be defined in future preclinical studies focused on tolerability, safety, and efficacy. A significant parameter to be defined is how to reach a level of erythrophagocytosis in the liver sufficient to achieve consistent liver protection while avoiding severe hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…This results in antitumor responses surpassing immune reactivity toward the initial targeted epitope. 226 5.5. Fc Receptors.…”
Section: Cd40 Cd40 (Bp50 Tnfrsf5mentioning
confidence: 99%
“…Therefore, it cannot be concluded whether antigen fate or DC maturation induced by CD40 targeting was the main determinant for the enhanced T cell proliferation. Of note, an exciting prospect in the context of CD40 targeting are bispecific antibodies recognizing CD40 and a TAA. , These constructs bring tumor debris in proximity to CD40 + cells, which can take up, process, and present the tumor antigens, while simultaneously being stimulated via CD40. This results in antitumor responses surpassing immune reactivity toward the initial targeted epitope …”
Section: Promoting Pan-apc Antigen Presentationmentioning
confidence: 99%